Lebanon : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Lebanon. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that economic developments in Lebanon in 2006 were significantly affected by the July-August conflict with Israel. Real GDP is estimated to have been flat, with strong growth in the first half of the year offset by the disruptions during and after the conflict. Inflation increased, mainly reflecting supply shortages during the conflict and the ensuing blockade. Executive Directors have welcomed the authorities' success in containing the primary fiscal deficit in the first half of 2007.